Synthesis and Characterization of Transition Metals Derivatives of the Keggin Type Anion [Xn+W12O40]— (8-n) - Dey, K.C.; Sharma, V. (Asian Journal of Chemistry, 2010)
The heteropoly compound with molecular formula Na9[Cu(II)- Fe(III)W(VI)11O40]·21H2O (1) and Na6[Cu(II)Mo(VI)W(VI)11O40]· 11H2O (2) have been synthesized from an aqueous acetate buffer solution (pH = 4) containing sodium tungstate, copper chloride, ferric chloride and (pH = 3.8) containing sodium molybdate, sodium tungstate, copper chloride, respectively by replacing XO4 tetrahedron and MO6 octahedron from Keggin anion [XM12O40]–n. The compounds are separated as light blue crystals. Both the compounds 1 and 2 have two heteroatoms, one is central and other is peripheral, thus mixed heteropoly compounds. The substituted diheteropoly compounds are characterized by elemental analyses, IR studies, thermal analyses and molecular weight determination.